Maternal and Perinatal Outcome in Women with Systemic Lupus Erythematosus: A Retrospective Bicenter Cohort Study - Sylvia J. Kroese; Carolien N. H. Abheiden; Birgit S. Blomjous; Jacob M. van Laar; Ronald W. H. M. Derksen; Irene E. M. Bultink; Alexandre E. Voskuyl; A. Titia Lely; Marjon A. de Boer; Johanna I. P. de Vries; Ruth D. E. Fritsch-Stork (Journal of Immunology Research)
Objective. To investigate disease activity around and during pregnancy and pregnancy outcome in women with systemic lupus erythematosus (SLE) considering antiphospholipid antibody status. Moreover, differences between first and consecutive pregnancies were examined. Methods. Pregnancies > 16 weeks gestation of SLE patients receiving joint care from rheumatologists and gynecologists in two tertiary centers in the Netherlands between 2000 and 2015 were included. Disease activity, flare rate, and pregnancy outcomes and complications were assessed. Results. Ninety-six women (84% Caucasian) with 144 pregnancies were included. The median SLE(P)DAI score was 2 before, during, and after pregnancy. Flare rates were 6.3%, 20.1%, and 15.3%, respectively. Severe hypertensive disorder of pregnancy, intrauterine fetal death, preterm birth, and small-for-gestational age infants occurred in 18.1%, 4.1%, 32.7%, and 14.8%, respectively. Complication rates were similar in the first and consecutive pregnancies. Half of the women did not experience any pregnancy complication whereas 42.7% developed a complication during all pregnancies. Mean number of pregnancies was 2.4 and live births 1.7. Conclusion. In this SLE population with low disease activity, pregnancy complications were present irrespective of antiphospholipid antibody status. Furthermore, there were no differences in complication rates between the first and consecutive pregnancies as seen in healthy mothers. This information is useful for patient counseling.